Performance of Protective Clothing 1986
DOI: 10.1520/stp17308s
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Selected Work Fabrics as Barriers to Pesticide Penetration

Abstract: The effectiveness of seven work fabrics as barriers to three volumes of four carbon-14-labeled pesticides was determined in a controlled laboratory study. Significant differences were found for fabric, pesticide, and volume. Three laminate fabrics offered significantly better protection against the pesticides tested than fabrics now worn for pesticide application. The test fabrics were least effective barriers against parathion and Guthion and most effective barriers for paraquat. In general, as the volume inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The results of this laboratory study indicated that Gore-Tex fabric, which has been shown to be an effective barrier to the pesticides Guthion, parathion, paraquat, and dinoseb [2,8], offered similar thermal comfort as clothing worn by independent growers. Further research is needed to determine the barrier effectiveness of Gore-Tex fabric to a wilder range of pesticides, formulations, and concentration levels.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The results of this laboratory study indicated that Gore-Tex fabric, which has been shown to be an effective barrier to the pesticides Guthion, parathion, paraquat, and dinoseb [2,8], offered similar thermal comfort as clothing worn by independent growers. Further research is needed to determine the barrier effectiveness of Gore-Tex fabric to a wilder range of pesticides, formulations, and concentration levels.…”
Section: Discussionmentioning
confidence: 87%
“…Tyvek and Gore-Tex had previously been shown to have excellent resistance to pesticide penetration ; chambray was selected as the third fabric despite its poor resistance to pesticide penetration [2,8], since it is frequently worn by growers during pesticide application. Tyvek is a disposable polyethylene-coated 100% spun-bonded olefin fabric.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation